No Benefit of Adductor Canal Block Compared with Anterior Local Infiltration Analgesia in Primary Total Knee Arthroplasty: A Single-Blinded Randomized Controlled Clinical Trial. (1st February 2023) - Pic, Caroline; Macabeo, Caroline; Waissi, Emran; Lasselin, Philippe; Raffin, Mahé; Pradat, Pierre; Lalande, Laure; Lustig, Sebastien; Aubrun, Frederic; Dziadzko, Mikhail
Abstract : Background: An adductor canal block (ACB) performed by an anesthesiologist is an established component of analgesia after total knee arthroplasty. Alternatively, surgeons may perform periarticular local infiltration analgesia (LIA) intraoperatively. We hypothesized that ACB would be superior to anterior LIA in terms of morphine consumption in the first 48 hours after primary total knee arthroplasty under spinal anesthesia. Methods: This prospective controlled and blinded trial included 98 patients; 48 received an ACB plus sham (saline solution) anterior LIA, and 50 received a sham (saline solution) ACB plus anterior LIA. Both groups received posterior LIA with local anesthetic. The primary outcome was cumulative morphine consumption at 48 hours after surgery. Secondary outcomes were pain while resting, standing, and walking, rehabilitation scores, opioid-related side effects, and patient satisfaction. Results: No difference in the primary outcome was found, and the 48-hour morphine consumption was low in both arms (28.8 ± 17.6 mg with ACB, 26.8 ± 19.2 mg with anterior LIA; p = 0.443). Pain scores were significantly better in the anterior LIA arm, but the differences were not clinically relevant. There were no differences in any other secondary outcome measures. Conclusions: LIA may be used as the primary option for multimodal postoperative pain management in patients undergoing primary total knee arthroplasty with spinal anesthesia. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.